2021
DOI: 10.3389/fnut.2021.739766
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index, Diabetes, and Risk of Tuberculosis: A Retrospective Cohort Study

Abstract: Although both diabetes mellitus (DM) and underweight are associated with increased risk of tuberculosis (TB), there are limited data evaluating TB risk while considering two factors simultaneously—body mass index (BMI) and DM. A retrospective cohort study was performed with 10,087,903 participants of the Korean National Health Screening Program in 2009. The cohort was followed up to the date of TB incidence, death, or until December 31, 2018. We compared the incidence and risk of TB according to BMI category a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
23
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 32 publications
1
23
1
Order By: Relevance
“…Our finding is not different from the study done in the past and explains that BMI is significantly associated with pulmonary TB [33]. Moreover, a study done in 2017 found that lower BMI is positively associated with PTB [34].…”
Section: Discussioncontrasting
confidence: 61%
“…Our finding is not different from the study done in the past and explains that BMI is significantly associated with pulmonary TB [33]. Moreover, a study done in 2017 found that lower BMI is positively associated with PTB [34].…”
Section: Discussioncontrasting
confidence: 61%
“…BMI as an indicator of the nutritional level of low body weight is widely used to assess the malnutrition grade of TB patients. 20,[22][23][24][25] However, there are still various types of malnutrition in clinics, such as total protein malnutrition, albumin malnutrition, nutritional anemia, and vitamin-related malnutrition. [26][27][28][29][30][31] .…”
Section: Discussionmentioning
confidence: 99%
“…The data on alcohol consumption, regular physical activity, and residential area were also determined by self-administered questionnaires. Categories for each variable were as follows: none (0 g/day), mild (<30 g/day), and heavy (≥30 g/day) for alcohol consumption; regular (>30 min of moderate physical at least 5 times per week or >20 min of strenuous physical activity at least 3 times per week), and non-regular for physical activity; metropolitan, city, and rural for the residential area [ 17 ].…”
Section: Methodsmentioning
confidence: 99%